2018
DOI: 10.1002/bab.1635
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of autophagy and differentiation of myenteric interstitial cells of Cajal in the pathogenesis of gastric motility disorders in rats with functional dyspepsia

Abstract: Interstitial cells of Cajal (ICC), especially myenteric interstitial cells of Cajal (ICC-MY), are key to gastrointestinal motility. However, their role in the pathogenesis of functional dyspepsia (FD) is unclear. Therefore, autophagy and differentiation of ICC-MY were investigated to elucidate the pathogenesis of gastric motility disorder in FD. FD model was induced by chronic stress via tail clamping in rats, which was assessed by the vital signs of rats, gastric emptying rate result, and histology. The ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Based on the functions of ICCs in generating slow-wave potentials for GI movement, ICC dysfunction can cause many GI motility disorders [ 29 ]. FD is known as one of the representative diseases associated with dysfunction of ICCs [ 30 ]. Abnormal gastric slow waves have been observed in patients with FD via multichannel electrogastrography [ 31 ].…”
Section: Pathophysiologic Involvement Of Icc In Fdmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the functions of ICCs in generating slow-wave potentials for GI movement, ICC dysfunction can cause many GI motility disorders [ 29 ]. FD is known as one of the representative diseases associated with dysfunction of ICCs [ 30 ]. Abnormal gastric slow waves have been observed in patients with FD via multichannel electrogastrography [ 31 ].…”
Section: Pathophysiologic Involvement Of Icc In Fdmentioning
confidence: 99%
“…Pathological findings have shown that delayed gastric dysmotility is associated with degeneration of ICCs in both humans [ 32 ] and animals [ 33 ]. In an FD rat model induced by chronic stress via tail clamping, the levels of autophagic biomarkers in ICCs were increased, whereas the levels of differentiation biomarkers in ICCs, such as c-kit and SCF, were decreased [ 30 ]. Although the relationship between ICC dysfunction and FD has not been accurately elucidated, excessive autophagy and abnormal differentiation of ICCs seem to contribute to the pathogenesis of FD [ 11 ].…”
Section: Pathophysiologic Involvement Of Icc In Fdmentioning
confidence: 99%
“…15 Besides, a study by Zhang et al reported that excessive autophagy of myenteric ICCs may contribute to the pathogenesis of gastric motility disorder in functional dyspepsia. 16 Most importantly, Yan et al found that Aurantii Fructus Immaturus (Zhishi, ZS) and Atractylodis Macrocephalae Rhizoma (Baizhu, BZ)-containing serum significantly inhibited autophagy through inactivation of the PI3K/Akt/mTOR pathway in glutamic acid-stimulated ICCs. 17 Additionally, another research reported that the inflammasome plays a crucial role in gastrointestinal health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…FD is a representative disease of gastrointestinal motility disorder. ICC will be a possible direction to respond to FD in the future (Zhang et al, 2018). Hawthorn refers to the ripe fruit of Crataegus pinnatifida Bge in the Rosaceae family (Figure 1).…”
Section: Introductionmentioning
confidence: 99%